Eritema Nodosum Leprosum Berat pada Pasien Kusta Lepromatosa: Laporan Kasus - Pramudita, Adelia Wuri; Kariosentono, Harijono; Evanti, Annisa Marsha; Asaduddin, Aiman Hilmi (Cermin Dunia Kedokteran, 2024)
A case of a 58-year-old woman with lepromatous leprosy and severe ENL reaction is reported. The patient has symptoms of pustules for 1 year and the nodules were getting worse in the last week, accompanied by fever, joint pain, nausea, and vomiting. Physical examination revealed madarosis, infiltrates of both ears, and multiple painful erythematous nodules on the extremities and trunk. Slit skin smear examination showed bacterial index +3 and morphological index of 15%. Histopathological examination revealed neutrophil infiltration and vasculitis in the upper dermis. The patient was diagnosed with lepromatous leprosy and severe ENL reaction. The patient received multidrug therapy and methylprednisolone (62.5 mg/day), which was gradually reduced. The ENL reaction is caused by the deposition of M. leprae antigens and antibodies in small blood vessels, resulting in vasculitis and the release of enzymes that damage tissues. ENL reactions are commonly found in multibacillary MH and occur before, during, and after treatment. This reaction is mediated by cytokines produced by T-helper-2 (Th2). ENL reactions can cause disability.